2021
DOI: 10.3390/cancers13081941
|View full text |Cite|
|
Sign up to set email alerts
|

Biomarker-Guided Anti-EGFR Rechallenge Therapy in Metastatic Colorectal Cancer

Abstract: The prognosis of patients with metastatic colorectal cancer (mCRC) who progressed to the first and the second lines of treatment is poor. Thus, new therapeutic strategies are needed. During the last years, emerging evidence suggests that retreatment with anti-epidermal growth factor receptor (EGFR) monoclonal antibodies (MAbs) in the third line of mCRC patients, that have previously obtained clinical benefit by first-line therapy with anti-EGFR MAbs plus chemotherapy, could lead to prolonged survival. The rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 51 publications
0
48
0
Order By: Relevance
“…In the PaNama trial, reinduction therapy was more active and effective in patients who had received FU/LV compared to those who received FU/LV+anti-EGFR (ORR = 34.7% vs. 8.9%, PFS = 6.3 vs. 3.8 months, respectively). On the other hand, preclinical and clinical evidence suggests a potential role of anti-EGFR reintroduction beyond the second-line, particularly in patients selected with liquid biopsy (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the PaNama trial, reinduction therapy was more active and effective in patients who had received FU/LV compared to those who received FU/LV+anti-EGFR (ORR = 34.7% vs. 8.9%, PFS = 6.3 vs. 3.8 months, respectively). On the other hand, preclinical and clinical evidence suggests a potential role of anti-EGFR reintroduction beyond the second-line, particularly in patients selected with liquid biopsy (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…3.8 months, respectively). On the other hand, preclinical and clinical evidence suggests a potential role of anti-EGFR reintroduction beyond the second-line, particularly in patients selected with liquid biopsy ( 28 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have shown promising activity of reintroduction of anti-epidermal growth factor receptor (EGFR) drugs in patients with RAS wild-type ( RAS WT) metastatic colorectal cancer (mCRC), that obtained clinical benefit by first-line therapy with anti-EGFR drugs, then became resistant and progressed to second-line treatment [ 1 , 2 , 3 , 4 , 5 , 6 ]. This treatment strategy is called rechallenge.…”
Section: Introductionmentioning
confidence: 99%
“…So far, beside WT ctDNA at liquid biopsy analysis, several potential biomarkers have been investigated to predict the response to EGFRi rechallenge with discordant results [ 4 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%